Periodic Wavelets in Walsh Analysis - Farkov, Yu. A. (Communications in Mathematics and Applications, 2012)
The main aim of this paper is to present a review of periodic wavelets related to the generalized Walsh functions on the p-adic Vilenkin group G_p. In addition, we consider several examples of wavelets in the spaces of periodic complex sequences. The case p = 2 corresponds to periodic wavelets associated with the classical Walsh functions.